2020
DOI: 10.1051/0004-6361/202038150
|View full text |Cite
|
Sign up to set email alerts
|

Dust and gas in the central region of NGC 1316 (Fornax A)

Abstract: Context. The early-type galaxy NGC 1316, associated with the radio source Fornax A, hosts about 107 M⊙ of dust within a central radius of 5 kpc. These prominent dust structures are believed to have an external origin, which is also a popular interpretation for other dusty early-type galaxies. Moreover, it has been long known that ionised gas is present in NGC 1316, but to date there has been a lack of detailed investigation. Aims. Our aim is to understand the nature of ionised gas and dust in NGC 1316 and to o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Recently, Richtler et al (2020) presented the same observations focusing on the [N ii]λ6583 line and the NaI D absorption doublet. Our study presents both points of agreement and tension with the conclusions of these authors, as detailed in Sects.…”
Section: Ionised Gas Observationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, Richtler et al (2020) presented the same observations focusing on the [N ii]λ6583 line and the NaI D absorption doublet. Our study presents both points of agreement and tension with the conclusions of these authors, as detailed in Sects.…”
Section: Ionised Gas Observationsmentioning
confidence: 90%
“…A major merger occurred 1-3 Gyr ago (e.g., Schweizer 1980;Serra et al 2019). This event likely caused the first triggering of the radio source and brought large amounts of dust (Schweizer 1980;Lanz et al 2010;Galametz et al 2012;Duah Asabere et al 2016), molecular gas (Horellou et al 2001;Galametz et al 2014;Morokuma-Matsui et al 2019), and neutral hydrogen (Horellou et al 2001;Serra et al 2019;Richtler et al 2020;Kleiner et al 2021) into the centre and around the galaxy. Figure 1 shows that the dust seen in extinction in the innermost ≈8 kpc is distributed mainly in two structures: a stripe crossing the centre from the north-west to the south-east; and two outer arcs that seem to originate at the bend of the radio jets.…”
Section: Introductionmentioning
confidence: 99%
“…The EW-stripe is aligned with the major axis of the stellar body and is perpendicular to the dust lane, which may lead to misinterpret the nature of this feature as an edge-on circumnuclear disk (e.g. Richtler et al 2020) as seen in several active early-type galaxies, (e.g. NGC 1813 and PKSB 1718-649; Krajnović et al 2015;Maccagni et al 2016Maccagni et al , 2018.…”
Section: Distribution and Moment Maps Of The Ionised Gas In The Inner...mentioning
confidence: 99%
“…Schweizer 1980;Serra et al 2019). This event likely caused the first triggering of the radio source and brought large amounts of dust (Schweizer 1980;Lanz et al 2010;Galametz et al 2012;Duah Asabere et al 2016), molecular gas (Horellou et al 2001;Galametz et al 2014;Morokuma-Matsui et al 2019), and neutral hydrogen (Horellou et al 2001;Serra et al 2019;Richtler et al 2020;Kleiner et al 2021) into the centre and around the galaxy. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al 2010) and internal causes (e.g. Lauer et al 2005;Richtler et al 2020). Since M89 exhibits shells and stellar streams (Schweizer & Seitzer 1992;Bonfini et al 2018), the presence of dust (and gas, that is observed at larger radii) can be a signature of an accreted small stellar component that can have different characteristics (although diluted by the bulk of stars of M89).…”
Section: Comparison With Full Spectral Fitting Resultsmentioning
confidence: 99%